Lee Chong's Grocery - Unknown:::Creator::::::::::::
Sam Chan behind counter of Wing Chong Market on Cannery Row. Chan worked for Yee family for many years. Steinbeck called this Lee Chong's Heavenly Flower Grocery in Cannery Row and Sweet Thursday.